2009
DOI: 10.1213/ane.0b013e3181be371b
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lidocaine Decreased the Perioperative Opioid Analgesic Requirements but Failed to Reduce Discharge Time After Ambulatory Surgery

Abstract: Perioperative systemic lidocaine significantly reduces opioid requirements in the ambulatory setting without affecting time to discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 12 publications
4
45
0
2
Order By: Relevance
“…Kaba et al found that the total dose of sufentanil given to patients in the lidocaine group during laparoscopic colectomy was significantly lower than in the control group (13.0 ± 3.7 µg versus 16.3 ± 3.6 µg) [7]. A similar result was obtained in ambulatory surgery where lidocaine use yielded a 30% reduction in intraoperative opioid use [31]. In another study, in patients undergoing laparoscopic cholecystectomy, the total fentanyl consumption was found to be significantly lower in the lidocaine group (242 ± 48.5 µg vs 323 ± 70.8 µg) [32].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Kaba et al found that the total dose of sufentanil given to patients in the lidocaine group during laparoscopic colectomy was significantly lower than in the control group (13.0 ± 3.7 µg versus 16.3 ± 3.6 µg) [7]. A similar result was obtained in ambulatory surgery where lidocaine use yielded a 30% reduction in intraoperative opioid use [31]. In another study, in patients undergoing laparoscopic cholecystectomy, the total fentanyl consumption was found to be significantly lower in the lidocaine group (242 ± 48.5 µg vs 323 ± 70.8 µg) [32].…”
Section: Discussionmentioning
confidence: 81%
“…This observation is particularly important for patients with severe coronary artery disease. The protocol of administering a loading dose followed by a continuous IV infusion of lidocaine during general anesthesia has been used in several previous investigations [7,10,11,31,33]. The doses used are calculated to achieve a plasma lidocaine concentration well below the toxic levels (> 5 µg/ml) [7,21].…”
Section: Discussionmentioning
confidence: 99%
“…24 Seven studies originated in the USA, [25][26][27][28][29][30][31] one in Belgium, 32 two in Taiwan, 14,33 three in Germany, 23,34,35 one in New Zealand, 36 three in Sweden, [37][38][39] two in China, 40,41 one in France, 42 three in Canada, [43][44][45] one in Mexico, 24 two in Saudi Arabia, 46,47 one in Israel, 48 one in the Republic of Korea 49 and one in Finland. 50 Studies were conducted in patients undergoing abdominal, cardiac, thoracic, orthopedic, or urologic surgery ( Table 1).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…51 Twenty-six (90%) studies were placebo-controlled blinded studies. 14,[23][24][25][26][27][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][45][46][47][48][49] Primary outcomes…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation